2013
DOI: 10.1007/s10549-013-2597-8
|View full text |Cite
|
Sign up to set email alerts
|

A phase I dose escalation study to determine the optimal biological dose of irosustat, an oral steroid sulfatase inhibitor, in postmenopausal women with estrogen receptor-positive breast cancer

Abstract: Steroid sulfatase (STS) inhibition may have a therapeutic role in suppression of endocrine-responsive breast cancer. This study aimed to determine the optimal biological dose and recommended dose (RD) of the STS inhibitor irosustat. A three-part, open-label, multicenter, dose escalation study of irosustat in estrogen receptor-positive breast cancer patients involved administration of a single dose of irosustat with a 7-day observation period; followed by a daily oral dose of irosustat for 28 days; and an exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 9 publications
2
32
0
Order By: Relevance
“…Two phase I studies have demonstrated irosustat to be well tolerated and provided evidence of clinical activity (Stanway et al 2006, Coombes et al 2013.…”
Section: Ar Antagonists and Androgen Biosynthesis Inhibitors In Er-pomentioning
confidence: 99%
“…Two phase I studies have demonstrated irosustat to be well tolerated and provided evidence of clinical activity (Stanway et al 2006, Coombes et al 2013.…”
Section: Ar Antagonists and Androgen Biosynthesis Inhibitors In Er-pomentioning
confidence: 99%
“…In prostate cancer cell lines, androgen deprivation up-regulates the OATPs, to facilitate enhanced uptake and release of steroid conjugates [57]. Sulfatase inhibitors have been tested for prostate, breast and endometrial cancers, but have not yet found efficacy as a monotherapy [58, 59]. Recent evidence suggests a gain-of-function mutation stabilizes type 1 3β-hydroxysteroid dehydrogenase and may represent a putative therapeutic target in CRPC [60].…”
Section: 11 Intratumoral Androgen Conversion and Akr1c3 Inhibitionmentioning
confidence: 99%
“…This was a phase 2, multicenter, international, openlabel, randomized, 2-arm study of oral irosustat 40 mg/d (ie, the dose that was previously established in a phase 1, doseescalation study 21 ) versus oral megestrol acetate 160 mg/d. Participants were randomized 1:1 to receive either treatment until objective tumor progression, 2 years after the last patient was randomized (June 3, 2011), withdrawal, or death.…”
Section: Methodsmentioning
confidence: 99%